2010
DOI: 10.1002/cmdc.201000161
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fatty Acid Amides of Catechol Metabolites that Exhibit Antiobesity Properties

Abstract: A series of fatty acid amides of 3,4-methylenedioxymethamphetamine (MDMA) catechol metabolites were synthesized in order to evaluate their biological activities. Upon administration, all synthesized compounds resulted in negative modulation of food intake in rats. The most active compounds have affinity for the CB(1) receptor and/or PPAR-α; part of their biological activity may be caused by these double interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Previously, we have reported that acute administration of OLHHA significantly decreases food intake in food-deprived Wistar rats ( Almeida et al, 2010 ). In the present study, we performed a repeated treatment of this dihydroxyphenyl derivative in a genetic model of obesity and NAFLD, followed by initial assays related to cardio- and hepatotoxicity.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previously, we have reported that acute administration of OLHHA significantly decreases food intake in food-deprived Wistar rats ( Almeida et al, 2010 ). In the present study, we performed a repeated treatment of this dihydroxyphenyl derivative in a genetic model of obesity and NAFLD, followed by initial assays related to cardio- and hepatotoxicity.…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, the activation of hepatic CB 1 is associated with an increase of de novo fatty acid synthesis, and this lipogenic response is abolished by CB 1 blockade ( Osei-Hyiaman et al, 2005 ). Given that the endocannabinoid system plays a main role in the regulation of energy homeostasis and that it has also been reported that OLHHA has affinity for the CB 1 ( Almeida et al, 2010 ), we evaluated the gene expression of the different components of this system in the liver of Zucker rats. Consistent with previous reports showing that the endocannabinoid system is altered in peripheral tissues in obese rats ( Izzo et al, 2009 , 2010 ), our results showed that this signaling system was dysregulated in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider that the ether derivatives of hydroxytyrosol could have a significant importance in obesity management because appetite and lipid metabolism could be simultaneously regulated. 18 A new route for the synthesis of hydroxytyrosol ether derivatives ( Figure 3) with natural unsaturated derived fatty alcohols such as oleic and linoleic alcohol is proposed. It is postulated that newly synthesized compounds may have LDL antioxidant activity with a potency similar to that of hydroxytyrosol.…”
Section: ■ Introductionmentioning
confidence: 99%